Implementasi Algoritma Dijkstraa Berbasis Teori Graf untuk Penentuan Rute Terpendek dari STIKOM Tunas Bangsa ke Suzuya Merdeka Mall Kota Pematangsiantar - Winda Pasaribu; Christinauli Purba; Yonatan.s; Indra Gunawan (Jurnal Teknik Informatika dan Teknologi Informasi, 2026)
Determining the shortest route is an important problem in graph theory that is widely applied in digital navigation systems. This study aims to implement the Dijkstra algorithm based on graph theory to determine the shortest route from STIKOM Tunas Bangsa to Suzuya Merdeka Mall in Pematangsiantar City. The research method used is a quantitative approach by modeling the road network as a weighted graph, where vertices represent locations or road intersections and edges represent road segments with distance weights. Distance data between locations were obtained through observation and digital map data from Google Maps, which were then processed using the Dijkstra algorithm to calculate the minimum distance from the starting point to the destination. The results show that the Dijkstra algorithm is able to determine the shortest route systematically and efficiently. The optimal route obtained is A → B → C → D → L with a total distance of 690 meters. The comparison results with Google Maps indicate a distance similarity of 0.69 km with an accuracy level of 99%. Therefore, the Dijkstra algorithm is proven to be effective in solving the shortest path problem and has the potential to be implemented in web-based or mobile navigation systems.